Thelotrema maharashtrense (Graphidaceae), a new lichen-forming species from the Western Ghats of India - Ansil, Parayelil A.; Rajeshkumar, Kunhiraman C.; Lücking, Robert (Phytotaxa, 2026)
This study describes a new lichenized species, Thelotrema maharashtrense, from the Western Ghats of Maharashtra, India, integrating morphological, chemical, and phylogenetic methods. Thelotrema maharashtrense is characterised by a loosely corticate thallus, prominent apothecia with an only rarely apically free, basally I+ amyloid exciple, 1-spored asci producing large, muriform ascospores, and lack of lichen substances. Analyses based on a concatenated mtSSU, LSU and rpb2 data set placed T. maharashtrense in a well-supported monophyletic clade allied to T. adjectum. This is the first molecular phylogenetic study of Thelotrema from India.